A predicament of single mothers in micro-enterprise and government support policy: a study in Melaka Tengah district / Hani Nadiah Ismail - Ismail, Hani Nadiah (2016)
The role of single parents is very challenging especially when the family is headed by women. The issue of single mothers had become the main concern by the government because they were linked by the issue of poverty. Therefore, there are many efforts provided by the government to support single mothers in order for them to obtain reasonable income to support their family. The effort includes the encouragement of single mothers to be independent by involving in entrepreneurship especially in micro-enterprise. The purpose of this study is to investigate the predicaments faced by single mothers in micro-enterprise and also the government support policy that was provided for single mothers. This study will evaluate the internal and external challenges while conducting their micro-business and how they overcome the predicaments to sustain in the business. The model of this study was adapted from a Model of Entrepreneurial Success by Freese and Gielnik (2013). Then, the research method that is used in this study is mix method which relies on quantitative and qualitative research method. The data collection method for this study is by using questionnaire and series of interview session. The sampling technique used is purposive sampling technique and the target population is single mothers who are actively involved in micro-enterprise and was registered as members of single mothers associations in Melaka. After the data analysis was conducted, it was found that single mothers faced family and infrastructure problems most during conducting their business. With the help of single mothers association and the government supports, single mothers then can faced the challenges in order to achieve success in microenterprise business.